Clinical usage of intravenous immunoglobulin in neonates in a tertiary care centre: a retrospective observational study - Ghalige, Sharath S.; M., Vaideeswaran; S., Mangalabharathi (International Journal of Contemporary Pediatrics, 2019)
Background: Intravenous Immunoglobulin (IVIG) is a blood product manufactured from pooled plasma. With increasing availability, an increased usage in neonates is being noted, though its utilisation has not been audited thoroughly. The objectives of this study are to describe the usage pattern and indications of IVIG and its outcome in a state-run tertiary care NICU. Methods: This retrospective observational study was carried out at the inborn unit of Department of Neonatology, Madras Medical College, Chennai on a cohort of neonates who received IVIG over 3.5 years from January 2016 to June 2019. Data was collected from drug register, neonatal case records, exchange transfusion register and death register. Results: Our study cohort had 55 neonates who received IVIG over 3.5 years. Indications for IVIG usage were Rh-alloimmunisation (23), ABO-alloimmunisation (7), prophylaxis of perinatal varicella (20), and other immune thrombocytopenia (5). Among 30 neonates with ABO-/Rh-incompatibility, 11 required exchange transfusion (ET). ET rates have shown a decreasing trend during this period. 2 babies with Rh-immunisation and Hydrops expired. None of the babies given prophylaxis for perinatal varicella manifested the disease. Neonates treated for immune thrombocytopenia were successfully discharged. Conclusions: This study shows the IVIG usage pattern in a tertiary care neonatal unit. In neonates with Hemolytic disease due to Rh-/ABO-alloimmunisation treated with IVIG, a reduction in rates of exchange transfusion has been noted. IVIG is being used increasingly for prophylaxis of perinatal varicella and immune related thrombocytopenia with promising benefits. It is prudent to have SOPs for IVIG administration with standardised issue and transfusion forms for documentation to regulate its judicious use.